ANALISA BERAT VOLUME DAN KUAT TEKAN BATAKO DENGAN PENAMBAHAN FIBREGLASS - Wibowo, Petrus Haryanto; Hendi, Hendi (Jurnal Kajian Teknik Sipil, 2020)
The increasing population growth has caused the population's need for housing facilities to increase. The development of housing facilities will increase the need for building materials. The solution to resolve this issue is by working up the use of local resources to raise the production of necessary building materials. One of the building materials in this research is the concrete brick that is a relatively cheap and strong building block. Fiberglass is an industrial material for construction as part of the waterproofing that has a value of strength, economy, and flexibility in its use. Since it is known for its usefulness values, so the author conducted a study with the addition of fibreglass as a replacement of fine aggregate in the bricks to work on the volume weight and compressive strength. The research indicates that the addition of fiberglass was 0%, 2.5%, 5% & 7.5% in the concrete block with the volume weight values were 2208 kg/m3, 2149.037 kg/m3, 2130.568 kg/m3 & 2125.63 kg/m3. The value of volume weight on the addition of fibreglass to the concrete brick showed a smaller volume weight value than the normal brick. The research indicates that the addition of fiberglass is 0%, 2.5%, 5% & 7.5% in the brick with the average compressive strength values were 436.025 kg/cm2, 236.805 kg/cm2, 230.176 kg/cm2 & 289.129 kg/cm2. The average compressive strength in the addition of fiberglass to the concrete brick was smaller than the normal brick..